Effect of preoperative melatonin on anxiety and pain in patient undergoing phacoemulsification cataract surgery - N. Sarala; K. Bhuvana; T. Sangeetha; K. Kanthamani (Oman Journal of Ophthalmology, 2025)
INTRODUCTION: Preoperative anxiety is an unpleasant state in patients undergoing Phacoemulsification cataract surgery. Benzodiazepines are used to alleviate anxiety. The anxiolytic and analgesic effects of melatonin are compared with diazepam in this study. We have assessed the effect of melatonin on verbal anxiety score (VAS), verbal pain score (VPS), sedation score, intraocular pressure, and the adverse effects. MATERIALS AND METHODS: Patients were randomized to receive a tablet of melatonin 3 mg or diazepam 5 mg orally 90 min before surgery. At the preoperative visit, VAS and VPS, 0–10 were explained to patients. A sedation score 4-point scale was assessed. VAS was recorded before premedication (T1), 60 min after premedication (T2), during the operation period (T3), and also postoperatively in the recovery room (T4). Pain and sedation score (T2, T3, T4). Intraocular pressure (IOP) before premedication and after 24 h. The ophthalmologist scored the intraoperative conditions as excellent, good, and poor. RESULTS: A total of 199 patients were recruited. 99 received melatonin, 100 diazepam. Females 54 and males 45 with a mean age of 62 ± 8 and 65 ± 7 years in melatonin, 62 F and 38 M with a mean age of 61.9 ± 8, 63 ± 10, respectively. Blood pressure and pulse rate were comparable between groups at T1 and T4. VAS and sedation score with melatonin reduced significantly compared to diazepam at T2, T3, and T4 (P = 0.0001). VPS between melatonin and diazepam was similar at all-time points. Intraoperative condition was scored as excellent at 71% and 28% in melatonin and diazepam, respectively. IOP between groups was similar. CONCLUSION: Melatonin significantly reduced anxiety compared to diazepam with less sedation. Patient cooperation during the intraoperative period was better with melatonin.